The Correlation Between Parents’ Involvement and English Achievement of High School Students - Miyagi, Tri Utami; Supiah, Supiah; Sugiarto, Dody (EEdJ: English Education Journal, 2021)
This study was aimed to find out parents’ involvement on English achievement, the students’ English achievement, and the correlation between them of high school students in Pangkalpinang, Bangka. The research method used was quantitative with a correlational design. The sample of this study was 85 students from three classes. The data were collected from questionnaire about parents’ involvement and documentation from the report book score of the students which was collected from the English teacher. The data were analyzed by using Pearson Product-Moment Correlation. The result showed that the rxy (0.256) was higher compared to r-table at significant level 5% (0.213). It was considered that the alternative hypothesis (Ha) was accepted and null hypothesis (H0) was rejected. In conclusion, there was a significant correlation between between parents’ involvement, and students’ English achievement.